Social dimensions of distance postgraduate education in Greece (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Although distance learning has no less effectiveness than on campus education (Young J, 2000), is still unclear why Greek students adopt the HOU for their postgraduate studies. This research addresses the following questions: â€œWhat makes the Greek students to decide to pursue their postgraduate degree via the HOU instead of the on campus one? Which are the factors affecting their decision? Which are the most important of them?â€ This research followed the survey methodology with the use of email questionnaires which followed the snow ball technique, while the results were analysed by the Dedoose software. The findings indicated that reasons like financial needs, time, flexibility and job prospects are influencing students towards their decision, while factors like family and friends are the catalysts in that direction. Our analysis suggests that the results can help HOU understand that need to help students overcome their contemporary societal barriers towards a better future.